Penyuluhan kesehatan demam berdarah dangue di Kelurahan Pidada, Panjang Bandar Lampung - Yulendasari, Rika; Rilyani, Rilyani; Widodo, Slamet; Khairul Rizwan, Al; Rahmah Hidayah, Alisah; Herliza (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2023)
Background: Dengue Hemorrhagic Fever is a disease caused by the Dengue virus which is transmitted to humans through the bites of Aedes Aegypti and Aedes Albocpictus mosquitoes. According to the 2020 statistical data, the flood rate in Pidada is the highest from other long areas, for the population of the Pidada sub-district is the area with the highest population density after the northern and southern lengths according to BPS data in 2020. The things above are one of the risk factors for the emergence of mosquitoes. Aedes eagypti in the Pidada Village, Panjang District, Bandar Lampung, which is the trigger for dengue fever. Purpose: Respondents can know, understand, understand, be able to prevent the occurrence of DHF and how to control it. Method: the method in this counseling consists of the first stage of participant attendance, the second distribution of leaflets and snacks, the third explanation and presentation of counseling about DHF, the fourth question-and-answer session, the fifth distribution of door prizes, the six measurements, blood pressure, GDS, and temperature, and the last Lastly is documentation. Results: Respondents can know, understand, understand, able to prevent the occurrence of DHF and how to control it. Conclusion: Respondents can know about DHF and how to control it. Keyword: DHF; Education; Health Pendahuluan: Penyakit Demam Berdarah Dengue adalah penyakit yang disebabkan oleh virus Dengue ditularkan kepada manusia melalui gigitan nyamuk Aedes Aegypti dan Aedes Albocpictus. Menurut data statistic 2020 angka banjir di pidada yang paling tinggi dari wilayah panjang lainnya, untuk jumlah penduduk kelurahan pidada merupakan daerah dengan kepadatan penduduk yang terbanyak setelah panjang utara dan selatan menurut data BPS tahun 2020. Hal-hal diatas menjadi salah satu factor resiko timbulnya nyamuk aedes eagypti di Kelurahan Pidada Kecamatan Panjang Bandar Lampung yang menjadi pemicu penyakit DBD. Tujuan: Supaya responden dapat mengetahui, memahami, mengerti, mampu dalam mencegah terjadinya DBD dan cara pengendaliannya. Metode: Metode dalam penyuluhan ini terdiri dari tahapan pertama absensi kehadiran participant, kedua pembagian leaflet dan snack, ketiga penjelasan dan pemaparan penyuluhan tentang DBD, keempat sesi tanya-jawab, kelima pembagian doorprize, keenam pengukuran, tensi, GDS, dan suhu, dan yang terakhir adalah pendokumentasian. Hasil: Responden dapat mengetahui, memahami, mengerti, mampu dalam mencegah terjadinya DBD dan cara pengendaliannya. Simpulan: Responden dapat mengetahui tentang DBD dan cara pengendaliannya.